Role Department of Education in Increase Quality Public Schools in the Regions: A Study of District Education Offices Sragen Central Java - James Williams; Noviasanti Nurkartika (Institut Pendidikan Alfatah Mataram, 2026)
Study This aim For analyze role District Education Office Sragen , Central Java, in increase quality public schools in the region . Education is sector strategically decisive​ quality source Power human and power competition area , so that government area through The Department of Education has not quite enough answer big in ensure quality service education. Research This use approach qualitative descriptive with technique data collection through interview, observations, and documentation to party department, head school, and teachers. Research results show that District Education Office Sragen play a role significant as a regulator, facilitator, and evaluator in improvement quality education. Efforts made​ covering planning strategic education area, improvement teacher competence through training sustainable, rehabilitation means infrastructure, supervision academic and managerial, as well as evaluation based performance school. However, still there is various constraint like limitations budget , inequality facility interregional, as well as the need more coordination​ strong between stakeholders interests. Research This conclude that improvement quality public schools require integrated strategy, support​ sustainable policies, as well as multi- party collaboration between government region, schools, communities and government center. Findings This expected can become reference for taker policy in increase quality education area in a way equitable and sustainable